Production Precipitated Calcium Carbonate (PCC) using Continuous Stirred Bubble Reactor (CSBR) - Sari, Ellyta; Arief, Syukri; Zulhadjri, Zulhadjri; Desmiarti, Reni; Amir, Amelia; Ramadhani, Umi; Agtata, Shazvelia Dwi; Anggreini, Sri (CHEMICA: Jurnal Teknik Kimia, 2023)
Precipitated calcium carbonate (CaCO3) has advantages such as small white and fine particle size, high homogeneity, and uniformity of particle shape so it is a product that is much sought after by various types of industry. PCC synthesis must be accompanied by the use of an efficient type of reactor for the reaction. PCC can be synthesized via a carbonation method that utilizes CO2 gas. This research aims to optimize all processes that occur in the PCC production circuit using a CSBR reactor in the form of a tank reactor to optimize the PCC synthesis process from the previous reactor and accommodate the number of tools to be economical. This research aims to optimize all processes that occur in the PCC production circuit using a CSBR reactor in the form of a tank reactor to optimize the PCC synthesis process from the previous reactor and accommodate the number of tools to be economical. Based on the research results, the PCC synthesis process is influenced by the type of solvent, temperature, CO2 gas flow rate, reaction time, and reactor type. The performance of the CSBR reactor was carried out using variations of R1, R2, R3, and R4 using the carbonation method, resulting in the highest purity and yield of 94.6% and 92.08%.